Advanced Water Management in PEFCs: Diffusion Layers with Patterned Wettability II. Measurement of Capillary Pressure Characteristic with Neutron and Synchrotron Imaging. Issue 9 (7th July 2016) - Forner-Cuenca, A.; Biesdorf, J.; Lamibrac, A.; Manzi-Orezzoli, V.; Büchi, F. N.; Gubler, L.; Schmidt, T. J.; Boillat, P.
Abstract : In this paper, we present an experimental study on the development of gas diffusion layer (GDL) materials for fuel cells with dedicated water removal pathways generated using radiation induced grafting of hydrophilic compounds onto the hydrophobic polymer coating. The impact of several material parameters was studied: the carbon substrate type, the coating load, the grafted chemical compound and the pattern design (width and separation of the hydrophilic pathways). The corresponding materials were characterized for their capillary pressure characteristic during water imbibition experiments, in which we also evidenced the differences between injection from a narrow distribution channel in the center of the material (and thus strongly relying on lateral transport) and homogeneous injection from one face of the material. All materials parameters were observed to have a significant influence on the water distribution. In particular, the type of substrate has a dramatic impact, with results ranging from a nearly perfect separation of water between hydrophilic and hydrophobic domains for substrates having a narrow pore size distribution to a fully random imbibition of the material for substrates having a broad pore size distribution.